Registration of new town or village greens : Proposed amendments to Schedule 1A (Exclusion of Right under section 15) to the Commons Act 2006 : Impact Assessment.: Proposed amendments to Schedule 1A (Exclusion of Right under section 15) to the Commons Act 2006 : Impact Assessment. (2014) - Great Britain., Department for Communities; Local Government,
No abstract available